The Development of Life Skills Based Career Guidance Module to Improve the Working Interest of Mentally Retarted Students in SMALB - Muh. Maaris Mubar; Triyanto Pristiwaluyo; Abdullah Sinring; Purwaka Hadi (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This study aims to develop a career guidance module based on life skills to increase work interest the mentally retarded students, and it is a Research and Development (R&D) with the Borg and Gall model, which has ten steps and was modified into eight steps. Data collection techniques used interviews and questionnaires. Data were analyzed using qualitative and quantitative descriptive methods. The results are: The level of the needs of module obtained from the initial data collection stage, the planning stage showed that teachers of skill subject needed teaching materials in the form of modules to provide life skills-based career guidance according to the conditions, potential and work interests of mentally retarded students; readability test of the initial design of the module was obtained from the development stage of the FGD activity with the results of the good category, and the initial product was continued to the validity test; Validity test conducted by two expert lecturers on materials and media using the Gregory formula showed the very valid validity results and limited trial stage using the content validity test of the Aiken V formula showed the very valid results. The final product is a life skills-based career guidance module to increase work interest in high school mentally retarded students.